Understanding Zika Virus Stability and Developing a Chimeric Vaccine through Functional Analysis - Xuping Xie (American Society for Microbiology, 2017)
ABSTRACT Compared with other flaviviruses, Zika virus (ZIKV) is uniquely associated with congenital diseases in pregnant women. One recent study reported that (i) ZIKV has higher thermostability than dengue virus (DENV [a flavivirus closely related to ZIKV]), which might contribute to the disease outcome; (ii) the higher thermostability of ZIKV could arise from an extended loop structure in domain III of the viral envelope (E) protein and an extra hydrogen-bond interaction between E molecules (V. A. Kostyuchenko, E. X. Y. Lim, S. Zhang, G. Fibriansah, T.-S. Ng, J. S. G. Ooi, J. Shi, and S.-M. Lok, Nature 533:425–428, 2016, https://doi.org/10.1038/nature17994 ). Here we report the functional analysis of the structural information in the context of complete ZIKV and DENV-2 virions. Swapping the prM-E genes between ZIKV and DENV-2 switched the thermostability of the chimeric viruses, identifying the prM-E proteins as the major determinants for virion thermostability. Shortening the extended loop of the E protein by 1 amino acid was lethal for ZIKV assembly/release. Mutations (Q350I and T351V) that abolished the extra hydrogen-bond interaction between the E proteins did not reduce ZIKV thermostability, indicating that the extra interaction does not increase the thermostability. Interestingly, mutant T351V was attenuated in A129 mice defective in type I interferon receptors, even though the virus retained the wild-type thermostability. Furthermore, we found that a chimeric ZIKV with the DENV-2 prM-E and a chimeric DENV-2 with the ZIKV prM-E were highly attenuated in A129 mice; these chimeric viruses were highly immunogenic and protective against DENV-2 and ZIKV challenge, respectively. These results indicate the potential of these chimeric viruses for vaccine development. IMPORTANCE Analysis of a recently observed high-resolution structure of ZIKV led to a hypothesis that its unusual stability may contribute to the associated, unique disease outcomes. Here we performed a functional analysis to demonstrate that viral prM-E genes are the main determinants for the high stability of ZIKV. The extra hydrogen-bond interaction (observed in the high-resolution structure) between ZIKV E proteins did not enhance virion stability, whereas the extended loop of E protein (CD loop in domain III) was essential for ZIKV assembly. More importantly, we found that a chimeric ZIKV with DENV-2 prM-E genes and a chimeric DENV-2 with ZIKV prM-E genes were highly attenuated in A129 mice. Mice immunized with these chimeric viruses generated robust neutralizing antibody responses and were fully protected from DENV-2 and ZIKV challenge, respectively, indicating that these chimeric viruses could be further developed as vaccine candidates.